Microscopic anatomy of the urinary bladder in newborns. - I. S. Kashperuk-Karpiuk; O. V. Tsyhykalo; I. Yu. Oliinyk (Морфологія, 2016)
Background. Characteristics of shape, size, position, age-related changes of the urinary bladder in humans is an important data for improving methods of prenatal diagnosis of congenital malformations. Objective. To study formation of the tissue layers of the bladder in dynamics of early neonatal period. Methods. Anthropometria – to detect the age of the objects examined; injection of the arterial vessels with further preparation under microscopic control – to study peculiarities of blood supply of the bladder; histological – to study peculiarities of the bladder wall; 3-D reconstruction method – to study spatial structure of the bladder. Results. Anatomical and histological features of the urinary bladder in newborns, and chronological order of its topographic-anatomical interrelations with adjacent organs and pelvic structures in dynamics of early neonatal period were detected; peculiarities of interrelations of the vessels and muscular structures of the bladder were estimated. Conclusion. New objective data on anatomy of the urinary bladder of newborns improve modern conception about age anatomy and changes in the structure of organs of the urinary system.